Equilibrium, Kinetic and Thermodynamic Study on Malachite Green dye Removal from Aqueous Solution using Activated Los Pantanos De Villa Nano Carbon - Murugan, S Om; Arivoli, S (IJRDO-Journal of Applied Science, 2017)
The research of the present work was to investigate the removal of Malachite Green dye from aqueous solution by using Los Pantanos De Villa Nano Carbon (ALPNC). Generally, dyes are used in chemical, textile, paper, printing, leather, plastics and various food industries. The need for the treatment of dye contaminated waste water passed out from the industry. In this study, Los Pantanos De Villa Nano Carbon was studied for its potential use as an adsorbent for removal of Malachite Green dye. The various factors affecting adsorption, such as initial dye concentration, contact time, adsorbent dose, effect of temperature and pH were evaluated. The experimental data were fitted into the pseudo-second order kinetic model. The equilibrium of adsorption was modeled by using the Langmuir and Freundlich isotherm models. The objective of the present work suggests the ALPNC may be utilized as a low cost adsorbent for Malachite Green dye removal from aqueous solution.